1985
DOI: 10.1093/bja/57.2.184
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Glycopyrrolate and Atropine in a Mixture With Neostigmine for Reversal of Neuromuscular Blockade

Abstract: Atropine and glycopyrrolate were compared in a mixture with neostigmine for reversal of neuromuscular blockade in patients undergoing open heart surgery. In patients not receiving beta-blocking drugs, glycopyrrolate was shown to possess advantages over atropine in terms of a lower initial increase in heart rate, better protection against the muscarinic effects of neostigmine, and smaller increases in rate-pressure product. The concomitant administration of beta-adrenergic blocking therapy significantly attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…However, one study reported that only 2% of patients who did not undergo premedication experienced excess secretion that required treatment 29 . Although the benefits and optimal dose of glycopyrrolate has been the subject of continuing debate [30][31][32] , this drug should be used judiciously because of its prolonged antisialagogue effect. The perception of thirst involves a number of components-including dry mouth, dry lips, thick tongue, thick saliva, dry throat, bad taste, and desire to drink water-which may have subtle distinctions 33 .…”
Section: Discussionmentioning
confidence: 99%
“…However, one study reported that only 2% of patients who did not undergo premedication experienced excess secretion that required treatment 29 . Although the benefits and optimal dose of glycopyrrolate has been the subject of continuing debate [30][31][32] , this drug should be used judiciously because of its prolonged antisialagogue effect. The perception of thirst involves a number of components-including dry mouth, dry lips, thick tongue, thick saliva, dry throat, bad taste, and desire to drink water-which may have subtle distinctions 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Anticholinergic drugs are often combined with neostigmine at the time of antagonism of the neuromuscular block. Several studies have demonstrated that glycopyrrolate is superior to atropine in this indication (8,64,65), because the faster onset of action of atropine results in initial tachycardia followed by a rapid fall in heart rate due to the onset of action of neostigmine, and postoperative bradycardia is more common because the duration of action of neostigmine is longer (66,67). Glycopyrrolate and neostigmine are both quaternary ammonium drugs, which have a parallel profile of pharmacodynamic actions; their onset of peak effects on heart rate is similar and so is the duration of action.…”
Section: Intravenous Administrationmentioning
confidence: 99%
“…It has been claimed that glycopyrrolate has a smaller effect on basal heart rate than that of atropine, based on clinical studies which were complicated by previous administration of drugs with muscarinic effects (e.g., atropine, pancuronium and anticholinesterases), varying depths of anaesthesia, or unequal doses of glycopyrrolate and atropine. [28][29][30][31][32][33] Undoubtedly, the fact that glycopyrrolate is prepared as a 0.2 mg. m1-1 solution whereas atropine is 0.6 mg. ml -~, further contributes to the clinical impression that glycopyrrolate is less potent than atropine on basal heart rate. It is important to realise that, in clinical studies which were more specifically designed to compare the effects of glycopyrrolate and atropine on basal heart rate, it has been shown that glycopyrrolate is at least as potent (if not more so) as atropine.…”
Section: Discussionmentioning
confidence: 99%